Examining the Need to Incorporate Halal Tourism into Conventional Tourism in North-Eastern Nigeria - Eldah Ephraim Buba (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This study examined the need to incorporate halal tourism into conventional tourism in north eastern Nigeria. The study examines how the perception of tourism is shaped in north-eastern Nigeria and the need for halal tourism in the region. The study employed the mixed method research design. It was carried out through the survey design with questionnaire and the use of secondary data. 180 respondents were randomly sampled across Adamawa, Borno, Taraba, Bauchi, Gombe and Yobe states for quantitative data while for qualitative data secondary data was used. Findings from the study shows that the resident’s clamour for halal tourisms in the region because the see some aspect of conventional tourism against their culture and religious belief. Areas that need halal tourism includes feeding, segregation of facilities from male and female and ban of drinking alcohol in tourism attractions. It is recommended that there is need to incorporate halal tourism into the components of tourism in the region. This can be done through the involvement of experts by tourism producers to ensure that the need of the people is included in the components of transportation, attraction and accommodation.